Increased Choroidal Blood Perfusion Can Inhibit Form Deprivation Myopia in Guinea Pigs - Zhou, Xuan; Zhang, Sen; Zhang, Guoyun; Chen, Yizhong; Lei, Yi; Xiang, Jing; Xu, Renchang; Qu, Jia; Zhou, Xiangtian (Investigative ophthalmology & visual science, 2020)
In guinea pigs, choroidal thickness (ChT) and choroidal blood perfusion (ChBP) simultaneously decrease in experimental myopia, and both increase during recovery. However, the causal relationship between ChBP and myopia requires further investigation. In this study, we examined the changes of ChBP with three different antimyopia treatments. We also actively increased ChBP to examine the direct effect on myopia development in guinea pigs. Experiment 1: Guinea pigs wore occluders on the right eye for two weeks to induce form-deprivation myopia (FDM). Simultaneously they received daily antimyopia treatments: peribulbar injections of atropine or apomorphine or exposure to intense light. Experiment 2: The vasodilator prazosin was injected daily into the form-deprivation eyes to increase ChBP during the two-week induction of FDM. Other FDM animals received appropriate control treatments. Changes in refraction, axial length, ChBP, ChT, and hypoxia-labeled pimonidazole adducts in the sclera were measured. The antimyopia treatments atropine, apomorphine, and intense light all significantly inhibited myopia development and the decrease in ChBP. The treatments also reduced scleral hypoxia, as indicated by the decrease in hypoxic signals. Furthermore, actively increasing ChBP with prazosin inhibited the progression of myopia, as well as the increase in axial length and scleral hypoxia. Our data strongly indicate that increased ChBP attenuates scleral hypoxia, and thereby inhibits the development of myopia. Thus ChBP may be a promising target for myopia retardation. As such, it can serve as an immediate predictor of myopia development as well as a long-term marker of it.